Efficient elimination of primary B-ALL cells in vitro and in vivo using a novel 4-1BB-based CAR targeting a membrane-distal CD22 epitope. Issue 2 (11th August 2020) - Velasco-Hernandez, Talia; Zanetti, Samanta Romina; Roca-Ho, Heleia; Gutierrez-Aguera, Francisco; Petazzi, Paolo; Sánchez-Martínez, Diego; Molina, Oscar; Baroni, Matteo Libero; Fuster, Jose Luis; Ballerini, Paola; Bueno, Clara; Fernandez-Fuentes, Narcis; et al.
Abstract : Background: There are few therapeutic options available for patients with B-cell acute lymphoblastic leukemia (B-ALL) relapsing as CD19 – either after chemotherapy or CD19-targeted immunotherapies. CD22-chimeric antigen receptor (CAR) T cells represent an attractive addition to CD19-CAR T cell therapy because they will target both CD22 + CD19 – B-ALL relapses and CD19 – preleukemic cells. However, the immune escape mechanisms from CD22-CAR T cells, and the potential contribution of the epitope binding of the anti-CD22 single-chain variable fragment (scFv) remain understudied. Methods: Here, we have developed and comprehensively characterized a novel CD22-CAR (clone hCD22.7) targeting a membrane-distal CD22 epitope and tested its cytotoxic effects against B-ALL cells both in in vitro and in vivo assays. Results: Conformational epitope mapping, cross-blocking, and molecular docking assays revealed that the hCD22.7 scFv is a high-affinity binding antibody which specifically binds to the ESTKDGKVP sequence, located in the Ig-like V-type domain, the most distal domain of CD22. We observed efficient killing of B-ALL cells in vitro, although the kinetics were dependent on the level of CD22 expression. Importantly, we show an efficient in vivo control of patients with B-ALL derived xenografts with diverse aggressiveness, coupled to long-term hCD22.7-CAR T cell persistence. Remaining leukemic cells at sacrifice maintained full expression of CD22, ruling out CAR pressure-mediated antigen loss. Finally, the immunogenicity capacity of this hCD22.7-scFv was very similar to that of other CD22 scFv previously used in adoptive T cell therapy. Conclusions: We report a novel, high-affinity hCD22.7 scFv which targets a membrane-distal epitope of CD22. 4-1BB-based hCD22.7-CAR T cells efficiently eliminate clinically relevant B- CD22 high and CD22 low ALL primary samples in vitro and in vivo. Our study supports the clinical translation of this hCD22.7-CAR as either single or tandem CD22–CD19-CAR for both naive and anti-CD19-resistant patients with B-ALL.